Laser-assisted biofabrication in tissue engineering and regenerative medicine. Issue 1 (19th December 2016) - Koo, Sangmo; Santoni, Samantha M.; Gao, Bruce Z.; Grigoropoulos, Costas P.; Ma, Zhen
Abstract: Abstract : Controlling the spatial arrangement of biomaterials and living cells provides the foundation for fabricating complex biological systems. Such level of spatial resolution (less than 10 µm) is difficult to be obtained through conventional cell processing techniques, which lack the precision, reproducibility, automation, and speed required for the rapid fabrication of engineered tissue constructs. Recently, laser-assisted biofabrication techniques are being intensively developed with the use of computer-aided processes for patterning and assembling both living and nonliving materials with prescribed 2D or 3D organization. In this review, we discuss laser-assisted fabrication methods, including laser tweezers, multi-photon polymerization, laser-induced forward transfer (LIFT), matrix assisted pulsed laser evaporation (MAPLE), and laser ablation as well as their applications in biological science and biomedical engineering. These advanced technologies enable the precise manipulation of in vitro cellular microenvironments and the ability to engineer functional tissue constructs with high complexity and heterogeneity, which serve in regenerative medicine, pharmacology, and basic cell biology studies.